Understanding about glanders among students at Institute of Molecular Biology and Biotechnology, Bahauddin Zakariya University, Multan, Pakistan - Muhammad Hamad Saif; Muhammad Imran Qadir (Open Journal of Bacteriology - Peertechz Publications, 2019)
Objective of present study was to understand the knowledge of students about infection, causes and cure of glanders. Glanders is an infection in humans and in animals. It is a bacterial disease caused by Burkholderia mallei. Glanders is mainly a disease which affect on horses, and some time cats, rabbits, humans or other animals. People are infected by direct contact with infected animals. The peoples have been suffered by glanders and it affect on their nasal discharge, saliva and in urine. Important information was collected by many questions e.g. is glanders a bacterial or viral, genetic or metabolic? 200 students participated in this project.